An analysis of the hot topics in the research on community group buying in China: From the perspective of visualization of co-word analysis - Dan, Li; Azman, Norhidayah Binti (Edelweiss Applied Science and Technology, 2025)
This study employs the co-word analysis method to systematically and quantitatively analyze the published literature in the field of community group buying in China. Bibliographic data were preprocessed using SATI software to generate a keyword co-occurrence matrix. Subsequently, tools such as SPSS and UCINET were utilized to perform word frequency analysis, cluster analysis, multidimensional scaling, and social network analysis, facilitating a visual representation of research hotspots. The data reveal that high-frequency keywords in current community group buying research can be categorized into three core areas: community group buying during the epidemic, operational strategies under the new retail background, and platform supervision. Among these, research on community group buying during the epidemic is relatively mature, while studies on operational strategies under the new retail environment are increasing. However, there are notable weaknesses in the supervision of community group buying platforms, indicating that both the breadth and depth of research in this area need to be strengthened to address existing challenges effectively.